2001
DOI: 10.1348/014466601164939
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Theory of Planned Behaviour: A meta‐analytic review

Abstract: The Theory of Planned Behaviour (TPB) has received considerable attention in the literature. The present study is a quantitative integration and review of that research. From a database of 185 independent studies published up to the end of 1997, the TPB accounted for 27% and 39% of the variance in behaviour and intention, respectively. The perceived behavioural control (PBC) construct accounted for significant amounts of variance in intention and behaviour, independent of theory of reasoned action variables. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

558
6,104
124
194

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 7,704 publications
(6,980 citation statements)
references
References 172 publications
558
6,104
124
194
Order By: Relevance
“…The relationship between attitudes/beliefs, intentions and behaviour is well established (e.g. 44, 45), and health professionals are no exception 46. This review highlights the potential for such attitudes to present a barrier to integrate smoking cessation interventions effectively into treatment for mental illnesses and substance use disorders.…”
Section: Discussionmentioning
confidence: 96%
“…The relationship between attitudes/beliefs, intentions and behaviour is well established (e.g. 44, 45), and health professionals are no exception 46. This review highlights the potential for such attitudes to present a barrier to integrate smoking cessation interventions effectively into treatment for mental illnesses and substance use disorders.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings are compatible with the meta‐analysis by Webb and Sheeran (2006), which concluded that the link between intention and behaviour is much weaker than previously assumed (cf. Armitage & Conner, 2001). The authors found that interventions that had a large effect on individuals' intentions only produced a small change in behaviour that can be attributed to the intentional control of behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies provide support for the utility of the model in the prediction of behaviour (Armitage & Conner, 2001;Godin & Kok, 1996). In the context of fruit and vegetable intake, the model has been reported to account for an average of 41% of the variance in intention and 45% of the variance in behaviour (Guillaumie, Godin, & Vézina-Im, 2010).…”
Section: Tpbmentioning
confidence: 95%
“…The extent to which PBC has a direct influence on behaviour is often thought to reflect an individual's actual behavioural control over the target behaviour (Fishbein & Ajzen, 2010). Given the difficulty in directly assessing actual behaviour control for most health related behaviours, PBC is used as a proxy for actual behaviour control the majority of TPB based studies (Armitage & Conner, 2001;Fishbein & Ajzen, 2010;Godin & Kok, 1996).…”
Section: Tpbmentioning
confidence: 99%
See 1 more Smart Citation